DEVELOPING PROFESSIONAL COMPETENCE OF FUTURE ENGINEERS THROUGH THE APPLICATION OF COMPUTER TECHNOLOGIES IN PHYSICS (American Journal of Pedagogical and Educational Research, 2026)
Physical sciences play a fundamental role in modern engineering education. The application of computer technologies in the process of teaching physics, particularly modeling, simulation, and digital analysis tools, serves as an effective means of developing students' professional competence. This article examines the pedagogical and scientific effectiveness of computer technologies in physics education based on the analysis of scientific sources indexed in the Scopus database. The research results indicate that computer modeling and simulation approaches enhance students' analytical thinking, problem-solving abilities, and digital literacy. Additionally, the theoretical foundations for developing the professional competence of future engineers through interdisciplinary integration are identified.